Prediction of Large Enhancement of Electron Mobility in Direct Gap Ge1−xSnx Alloy. Issue 11 (7th August 2017) - Mukhopadhyay, Bratati; Sen, Gopa; Basu, Rikmantra; Mukhopadhyay, Shyamal; Basu, Prasanta Kumar
Abstract : Group IV semiconductor‐based alloy Ge1− x Sn x can be grown on Si platform and a crossover from indirect (L valleys) to direct gap (Γ valley) occurs for x > 0.08. The direct gap alloy shows promise for use in high‐speed electronic and photonic devices. An earlier study predicted that the electron mobility in the alloy would increase by a few orders of magnitude above the value for pure Ge. In that work, however, electrons were assumed to occupy only the low effective mass Γ valley and only the deformation potential acoustic phonon and alloy scatterings were considered. In the present work, we give a more realistic estimate of the values of electron mobility in direct gap GeSn alloy, considering the Γ and L valleys and the phonon (deformation potential acoustic, optical and intervalley), alloy, and impurity scatterings. The effect of strain, both tensile and compressive, on the mobility is also studied. It is found that for higher alloy composition and suitable strain, mobility values ∼2 × 10 5 cm −2 /V · s, more than 50 times higher than the value in pure Ge (3900 cm 2 /V · s) may be achieved. This is attributed to increased separation between Γ and L valleys and consequent reduction in intervalley scattering. Abstract : The electron mobility in direct gap Ge1− x Sn x alloy has been calculated by considering Γ and L valleys and phonon, alloy disorder and impurity scattering mechanisms. Highest value is ∼2 × 10 5 cm −2 /V · s at x = 0.2 for unstrained bulk and tensile‐strained alloy layer.